Identifying Work Capacity and Promoting Work: A Strategy for Modernizing the SSDI Program. Issue 1 (November 2019) - Maestas, Nicole
The Social Security Disability Insurance (SSDI) program, which provides income support to individuals who become unable to work because of a disability, has not been substantially reformed since the 1980s, despite sweeping changes in health, medical technology, and the functional requirements of jobs. I review how the SSDI program works, its history in terms of caseloads and reforms, and findings from the research evidence that offer lessons for the future. I then propose two interlocking reforms that would modernize the core functions of the program. The first is to improve SSDI's process for determining whether an applicant has remaining capacity to work by replacing the outdated medical-vocational "grid" with a new system of individual work capacity measurement. Second, I propose the introduction of partial disability benefits, which would make use of the new system for measuring work capacity and allow beneficiaries to combine benefit receipt with work. Partial benefits could be paired with a generalized benefit offset to further encourage work by beneficiaries, and the Social Security Administration's complex array of work-related rules could be eliminated.